Narasi Kebijakan Makan Bergizi Gratis di Media Sosial Pemerintah Indonesia: Perspektif Truth and Language Martin Heidegger - Velisia Serenada; Fitzerald Kennedy Sitorus (CV. ITTC INDONESIA, 2026)
This study departs from the problem that communication of the Free Nutritious Meal policy on government social media functions not only as the delivery of information, but also as a space for constructing reality, public trust, and social meaning. The objective of this study is to analyse whether the language used by the government in communicating the Free Nutritious Meal policy is capable of authentically disclosing the reality of the programme or instead moves toward gerede, namely communication that circulates widely but loses existential depth. This study employs a qualitative approach with an interpretive paradigm. Data were collected through documentation of government social media content, official statements, news reports, and public responses related to the Free Nutritious Meal policy. The analysis technique used was interpretive textual analysis based on Martin Heidegger’s perspective of truth and language through the categories of aletheia, facticity, gerede, house of being, and concealment. The findings show that the government frames the Free Nutritious Meal programme through strategic and future oriented language, such as portraying it as an investment in the nation’s future. However, the narrative has not been fully aligned with the lived experiences of the public. Public criticism, negative sentiment, food safety concerns, governance issues, and demands for transparency indicate a gap between official discourse and implementation realities. Consequently, the language of the policy has not fully achieved aletheia because it has not been able to disclose the programme’s reality honestly and meaningfully. Instead, the communication tends to move toward gerede when formal messages circulate widely without adequately addressing public experience.